MOLECULAR IDENTIFICATION AND ANTIBIOGRAM OF METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS FROM WOUNDS OF BOTH IN- AND OUT-PATIENTS AT UNIVERSITY OF BENIN TEACHING HOSPITAL (UBTH), BENIN CITY, NIGERIA - Beshiru, Abeni; Uwhuba, Kate Enoh (FUDMA JOURNAL OF SCIENCES, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) stands as a prominent bacterial pathogen associated with various human infections, characterized by its remarkable ability to rapidly develop resistance to multiple antibiotics. The study aimed to characterize MRSA isolated from wounds among hospital patients. A total of eighty-seven unique S. aureus isolates were obtained from wound cultures collected from patients at the University of Benin Teaching Hospital (UBTH) in Benin City, Nigeria. These samples underwent assessment for methicillin resistance through conventional cultural methods, and detection of methicillin resistance (mecA) and S. aureus specific (nuc) genes using PCR amplification. The MRSA isolates underwent assessment for antimicrobial resistance through disc diffusion testing and for virulence factors using phenotypic testing procedures. An overall prevalence of 34/87 (39.1%) MRSA isolates was recorded. Based on the source of the isolate, the distribution of MRSA isolates from in-patients was 22/56 (39.3%) and out-patients was 12/31 (39.7%). Total Panton valentine leucocidin (PVL) screening revealed 11/34 (32.4%). All the isolates were resistant to penicillin 34/34 (100%) and cefepime 34/34 (100%). Lower level of resistance was demonstrated towards ciprofloxacin 3/34 (8.8%). Overall, every isolate displayed resistance to at least three antibiotics, resulting in a multiple antimicrobial resistance index of at least 0.33. The total virulence factors observed were beta-hemolytic activity 22/34 (64.7%), protease activity 14/34 (41.2%), and lipase activity 19/34 (55.9%). This study emphasized the significance of regularly monitoring MRSA prevalence within both the hospital and the local community. Therefore, the need for better intervention and continuous enlightenment on risks associated with the abuse...